The Influence of Cost Management and Human Resource Management (HR) on Operational Excellence Monitored Through the Balance Scorecard Framework - Fatria Asia Avanti; Mentiana Sibarani (Green Publisher Indonesia, 2025)
This study aims to analyze the influence of cost management and human resource management (HR) on operational excellence monitored through the Balance Scorecard framework in the oil and gas and limited energy industry in Indonesia. In facing the challenges of the energy transition towards Net Zero Emission 2060, oil and gas companies need to optimize operational efficiency through effective cost management and optimal human resource management. This study uses a quantitative approach with Exploratory Factor Analysis (EFA) and multiple linear regression techniques. Data was collected through a questionnaire of 71 respondents consisting of company leaders, managers, and operational staff in oil and gas and mining companies with at least 3 years of experience. The results showed that cost management had a significant effect on operational excellence with a regression coefficient of 0.454 (t-count = 4.941 > t-table = 1.9960). HR management has a stronger influence on operational excellence with a regression coefficient of 0.486 (t-count = 5.288 > t-table = 1.9960). Simultaneously, the two variables were able to explain 79.5% of the variance in operational excellence (R² = 0.795). The Balance Scorecard has proven to be effective as a holistic monitoring tool that integrates financial and non-financial aspects. This research provides a practical contribution for energy companies in optimizing operational strategies through the synergy of cost management and human resource management supported by a dynamic BSC monitoring system.